Asuhan Kebidanan Komprehenshif pada Ny.I Umur 26 Tahun GIP0A0 dengan Letak Obliqh di PMB Ny.S Wilayah Kerja Puskesmas Kaliwadas Tahun 2025 - Rizka Ayu Halimatussyafaah; Endang Susilowati; Surni’ah Surni’ah (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
Background:The maternal mortality rate according to WHO reaches 289.000/100.000 live births (2023). In ASEAN it is 137.000/100.000 live births (2023). In Indonesia it reaches 1.852/100.000 live births (2023). In central java, it is 2.261/100.000 live births (2023). In Brebes regency, there center 54 kasus (2023). Data from the kaliwadas community health center (2023) show no maternal mortality rate. Objective : To provide comprehensive midwifery care to mrs.I, 26 years old, with an oblique position using Varney 7 step midwifery management approach and SOAP documentation. Research method : Qualitative descriptive with case study approach. Problem formulation : Based on the background above, the problem formulation is “How is comprehensive midwifery care for mrs.I, 6 years old, GIP0A0 with oblique position in PMB Mrs.S, kaliwadas health center work area in 2025”. Results : Midwifery care for pregnancy that has been given to Mrs.I, 6 years old with an oblique position has been managed according to the mother’s needs for labor, newborns, postpartum and MAL family planning using a qualitative descriptive method with a case study approach. Conclusion : Comprehenshif midwifery care provided to mrs.I, 26 years old, with an oblique position was carried out in accordance with SOP, with the condition of the mother and baby being good